Perception of Environmental Education in school and the idea of well (Research, Society and Development, 2021)
Environmental education developed based on basic objectives, aiming to achieve the well-living, enables the construction of a society that is more responsible and prepared to deal with the existing adversities, both in the economic, social and environmental areas. Thus, through bibliographic research in scientific articles and literature related to this theme, some socio-educational actions developed in the school environment will be reported, with the objective of identifying and presenting possible solutions to the current problems present in society. Likewise, this study is intended to serve as a parameter for the emergence of new ideas and innovative actions related to environmental education in schools. The research includes descriptive, bibliographic and explanatory research methods, as well as a qualitative methodological approach, with the purpose of identifying the implementation of the proposal of well-living in the school environment, as a means of articulation and discussion, capable of promoting sustainability from a quality environmental education in schools.